A CHARACTERISTICS OF LINEARITY AND SENSITIVITY IN MEASURING THE MQ-4 SENSOR ON GAS LINE LEAKAGE - Arif Harjanto; Fatkhul Hani Rumawan; Didit Suprihanto; Haviluddin Haviluddin; Bangkit Bekti Nurdianto (Jurnal Teknik Informatika (Jutif), 2022)
A natural gas utilization with a domestic house-gas pipeline is essential. However, the house-gas installation pipe can cause a dangerous leak, so the house-gas leak detector is requires. This study aims to build and analyze a leak detector for natural gas flow on the stove using the MQ-4 gas sensor based on the house-gas linearity and sensitivity characteristics levels in the air with a threshold of 1000 ppm. Based on experimental, the sensor linearity value for the detected house-gas has been obtained in a correlation coefficient of 0.99 which indicates the sensor is quite sensitive in order to the house-gas detected. Then, the sensor sensitivity value has been acquired with the regression equation Y=-0.00449+(0.000481)X which means the voltage value at 0 ppm is around -0.00449 volts and increase at each ppm are 0.000481 volts with a value of 0.000481 volts with the effectiveness of the tools reaches 100%. Therefore, the study shown that the detection tools and systems can work properly.